Ethnomathematics in The Art of Barong Kemiren as Geometry Teaching Material - Lioni Anka Monalisa; Susanto Susanto; Saddam Hussen; Inggil Ismiharto (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2022)
Ethnomatematics is mathematics that is found in the culture of people who have unknowingly implemented mathematical concepts in their culture. The purpose of this qualitative research with an ethnographic approach is to describe ethnomathematics in the Barong Kemiren Art. The subjects of this study were three people, namely the head of the Barong Kemiren Arts, cultural observers who understand the history of the Barong Kemiren Arts and the dancers of the Barong Kemiren. Data collection methods used are observation, interviews, and documentation. The results of this study indicate that there is ethnomathematics in the Barong Kemiren Art. The geometric elements found include: flat shapes (triangles, squares, rectangles, and circles), spatial shapes (cubes, blocks, and tubes), congruence, and geometric transformations (reflections). Ethnomathematics in this study will be made worksheets with congruences material for class IX.